A disputed city: socio-environmental conflicts in Bogotá D. C. - Martínez Abello, Jairo Miguel (Universidad Distrital Francisco José de Caldas, 2023)
This article aims to present an overview of the different phenomena of socio-environmental conflict in the Bogota’s city, the capital of Colombia, since it can be seen in it the emergence of alternative, creative and resistant ways of interaction between communities and the nature, all against the depredation of environmental resources model. This presentation is carried out in four parts: i. by introduction, a conceptual approach to the phenomenon of environmental conflicts; ii. the methodological framework adopted; iii. It gives way to the presentation of the main results achieved so far by the investigation, namely: the forty environmental conflicts in the City; and iv. the general conclusions.